2008
DOI: 10.1002/ptr.2613
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of human P450 enzymes by natural extracts used in traditional medicine

Abstract: Different medicinal plants are widely used in Cuba and Mexico to treat several disorders. This paper reports in vitro inhibitory effects on the P450 system of herbal products commonly used by people in Cuba and Mexico in traditional medicine for decades. Experiments were conducted in human liver microsomes. The catalytic activities of CYP1A1/2, 2D6, and 3A4 were measured using specific probe substrates. The Heliopsis longipes extract exhibited a concentration-dependent inhibition of the three enzymes, and simi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(40 citation statements)
references
References 20 publications
2
38
0
Order By: Relevance
“…Besides the alteration of their own activity after metabolism (Cech et al, 2006), NAA containing plants (like Echinacea spp., Heliopsis spp., Piper spp., Capsicum spp.) and isolated NAAs with a terminal alkyne group inhibit P450 enzymes Pandit et al, 2012;Rodeiro et al, 2009;Subehan et al, 2006;Usia et al, 2006) and hence can also influence the metabolism of other drugs. Nevertheless, in-vitro as well as in-vivo studies showed this herb-drug interaction is clinically not significant (Toselli et al, 2009).…”
Section: Pk/pd Interactionsmentioning
confidence: 99%
“…Besides the alteration of their own activity after metabolism (Cech et al, 2006), NAA containing plants (like Echinacea spp., Heliopsis spp., Piper spp., Capsicum spp.) and isolated NAAs with a terminal alkyne group inhibit P450 enzymes Pandit et al, 2012;Rodeiro et al, 2009;Subehan et al, 2006;Usia et al, 2006) and hence can also influence the metabolism of other drugs. Nevertheless, in-vitro as well as in-vivo studies showed this herb-drug interaction is clinically not significant (Toselli et al, 2009).…”
Section: Pk/pd Interactionsmentioning
confidence: 99%
“…Effects of Cuban and Mexican herbal extracts used in traditional medicine (obtained from Heliopsis longipes, Mangifera indica L. and Thalassia testudinum) on CYP1A1/2 and other cytochromes involved in drug metabolism of CYP3A4 and CYP2D6 were studied with the use of human liver microsomes and compared with the pure constituents isolated from the extracts of affinin (an alkamide isolated from the H. longipes extract), N-iso-butyl-decanamide, and mangiferin. The extracts significantly inhibited CYP1A1/2 activities, which reflects the high content of flavonoids with recognized CYP1A1/2 inhibitory properties (Rodeiro et al, 2009).…”
Section: Other Natural Phenolsmentioning
confidence: 86%
“…Our previous in vitro results demonstrate that the extract from the marine plant T. testudinum can modulate CYP activities in cultured hepatocytes and human liver microsomes (Rodeiro et al 2008b, Rodeiro et al 2009). The present work provided the first in vivo evidence regarding the effects of this natural extract on the main CYP isoforms involved in the metabolism of several xenobiotics.…”
Section: Discussionmentioning
confidence: 98%
“…Previously we evaluated the effects of T. testudinum extract on the CYP enzymes activity in cultured rat hepatocytes and in human liver microsomes (Rodeiro et al 2008b, Rodeiro et al 2009). We observed a reduction in the activity of CYP2E1 in rat hepatocytes, while an increase in the activity of CYP2B1 was obtained after 48 hours of exposure.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation